2020
DOI: 10.1111/aje.12776
|View full text |Cite
|
Sign up to set email alerts
|

Amphibian assemblages and diversity patterns in two forest ecosystems of South‐Eastern Nigeria

Abstract: are equal first authorship/contributions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…A coral reef is an ecosystem that has important ecological functions in supporting the life of marine organisms. However, they are mostly affected by highly anthropogenic activities that directly influence the ecosystems and reef-associated marine organisms (Enochs, 2012;Damar et al, 2019;Rahman et al, 2020). Aside from these activities, another factor that also directly affects the environment is tourism.…”
Section: Introductionmentioning
confidence: 99%
“…A coral reef is an ecosystem that has important ecological functions in supporting the life of marine organisms. However, they are mostly affected by highly anthropogenic activities that directly influence the ecosystems and reef-associated marine organisms (Enochs, 2012;Damar et al, 2019;Rahman et al, 2020). Aside from these activities, another factor that also directly affects the environment is tourism.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, few researchers suggested using egg external features for turtle nest identification [ 18 , 19 ], whereas others argued it was ineffective due to overlapping egg diameters [ 20 ]. Like many other animal groups, recent studies showed the successful use of DNA barcoding in identifying herpetofauna [ 21 23 ]. Hence, we hypothesized that eggshells can be used as a source of DNA and in identifying freshwater turtle nests and species, including P .…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate anuran species conservation and management measures in protected and non‐protected areas rely on the knowledge of their biodiversity and habitat preferences (Boyd et al., 2008; Nneji et al., 2021; Rahman et al., 2020), therefore, understanding the consequences of habitat change for biodiversity is critical. Currently, protected area network is insufficient to safeguard the majority of species in the World (Stuart et al., 2004), and their persistence depends upon the effectiveness of conservation action plans (Daily, 2001; Onga'oa et al., 2013; Vandermeer & Perfecto, 2007).…”
Section: Introductionmentioning
confidence: 99%